High potential versus high performing employees - Juhdi, Nurita (s.n, 2012)
The objective of the study was to determine the major characteristics of high potential (HIPO) employees. Three hundred and twenty nine employees participated in the study. HIPO was mainly described by three major characteristics - high performance, learning agility and leadership spirit